Representasi Kebaya Jawa Pada Perempuan Dalam Serial “Gadis Kretek” - Aditian Alam Rizki; Anis Endang SM; Sri Narti (Universitas Dehasen Bengkulu, 2024)
Research purposes Indonesia, as an archipelagic country with vast cultural diversity, possesses various cultural heritages influenced by many civilizations. Traditional clothing, such as the kebaya, serves as an important symbol of local identity and culture. The film